Um olhar sobre o corpo em desfiles do design de moda Ronaldo Fraga no cenário corpocêntrico - ALMEIDA, Juliana Yuri Igarashi Ribeiro de (2018)
This dissertation investigates vectors related to body and appearance, implicated in the processes of subjectivation of the "corpocentric" scenario, through a cut in the field of Fashion Design. It focuses as an object of study, the fashion designer Ronaldo Fraga's parades, which give different perspectives to the body in this context. The Corps (Winter / 2002) parade introduces an analogy with the concept of "docile body", referring to those parades whose models obey the conventional patterns of the fashion system. In contrast to the explanation about the sculpted bodies that predominate in the castings, the parade The beaches continue waiting for both of us (summer / 2018), illuminates an approach on the diversity that pervades the bodies.